Competition for G beta gamma dimers mediates a specific cross-talk between stimulatory and inhibitory G protein alpha subunits of the adenylyl cyclase in cardiomyocytes - Hippe, Hans-Jörg; Lüdde, Mark; Schnoes, Katrin; Novakovic, Ana; Lutz, Susanne; Katus, Hugo; Niroomand, Feraydoon; Nürnberg, Bernd; Frey, Norbert; Wieland, Thomas (Naunyn-Schmiedeberg's archives of pharmacology, 2013)
Heterotrimeric G proteins are key regulators of signaling pathways in mammalian cells. Beyond G protein-coupled receptors, the amount and mutual ratio of specific G protein α, β, and γ subunits determine the G protein signaling. However, little is known about mechanisms that regulate the concentration and composition of G protein subunits at the plasma membrane. Here, we show a novel cross-talk between stimulatory and inhibitory G protein α subunits (Gα) that is mediated by G protein βγ dimers and controls the abundance of specific Gα subunits at the plasma membrane. Firstly, we observed in heart tissue from constitutively Gαi2- and Gαi3-deficient mice that the loss of Gαi2 and Gαi3 was accompanied by a slight increase in the protein content of the nontargeted Gαi isoform. Therefore, we analyzed whether overexpression of selected Gα subunits conversely impairs endogenous G protein α and β subunit levels in cardiomyocytes. Integration of overexpressed Gαi2 subunits into heterotrimeric G proteins was verified by co-immunoprecipitation. Adenoviral expression of increasing amounts of Gαi2 led to a reduction of Gαi3 (up to 90 %) and Gαs (up to 75 %) protein levels. Likewise, increasing amounts of adenovirally expressed Gαs resulted in a linear 75 % decrease in both Gαi2 and Gαi3 protein levels. In contrast, overexpression of either Gαi or Gαs isoform did not influence the amount of Gαo and Gαq, both of which are not involved in the regulation of adenylyl cyclase activity. The mRNA expression of the disappearing endogenous Gα subunits was not affected, indicating a posttranslational mechanism. Interestingly, the amount of endogenous G protein βγ dimers was not altered by any Gα overexpression. However, the increase of Gβγ level by adenoviral expression prevented the loss of endogenous Gαs and Gαi3 in Gαi2 overexpressing cardiomyocytes. Thus, our results provide evidence for a novel mechanism cross-regulating adenylyl cyclase-modulating Gαi isoforms and Gαs proteins. The Gα subunits apparently compete for a limited amount of Gβγ dimers, which are required for G protein heterotrimer formation at the plasma membrane.